MORDENITE IN THE PERMO-CARBONIFEROUS DEPOSITS OF THE MIDDLE COURSE OF THE PODKAMENNAYA TUNGUSKA - Larichev A.I.; Matviyenko N.I.; Van A.V. (My University, 1989)
The authors have discovered in the Katanga-Tetere interfluve extensive reserves of mordenite, produced by post-sedimentary transformation of ashy tuffs of intermediate composition. The particle-size distribution of the ash shows that most of it is of silt dimensions, indicating remoteness from the volcanoes that erupted it, as well as the possibility that it accumulated over a vast area. The great thickness of the partings of zeolitized tuff suggests very powerful explosive eruptions. The discovery of new shows of zeolites on the middle course of the Podkamennaya Tunguska has pushed the boundary of occurrence of high-silica zeolites substantially to the north of the well known Yenisey-Vilyuy zeolite province, where zeolite mineralization originated from Early Carboniferous ashy rocks and is areally confined to the basin of the same name that runs from the Rybinsk to the Kempendyayi basins, each which contains known shows and deposits of clinoptilolite. The great thickness of the mordenitized ashy tuff and its occurrence at several depths in the Permo-Carboniferous sequence suggest the presence of zeolite deposits in the Sobinsk area and the great potential of the Katanga saddle for mordenite accessible to exploitation.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная